An edge thinning algorithm based on newly defined single‐pixel edge patterns. Issue 4 (30th November 2022) - Ren, Lijuan; Wang, Xionghui; Wang, Nina; Zhang, Guangpeng; Li, Yongchang; Yang, Zhijian
Abstract: To improve the uniformity of one‐pixel width and continuity of the thinned edges, this paper proposes an edge thinning algorithm acting on grey‐scale edge images based on 24 self‐defined single‐pixel connection patterns. First, for binary or blurred grey‐scale gradient edge images, a distance–greyscale coupling algorithm is proposed to achieve gradient enhancement in the edge width direction. Then the elimination rules of noise points and gradient calculation method are given. Secondly, the marking rules of the first three pixels of each edge are given. The next pixel to be marked must meet that the new last three pixels belong to the 24 connection modes. Whether the qualified pixels are retained depends on its grey value and the local edge gradient. The algorithm is tested on four types of images. The results show that the proposed method can guarantee uniform, smooth, and connected one‐pixel‐wide lines that lie at the centre of the initial edges. The algorithm and the existing algorithms are performed on portrait image and four scenarios of the indoor datasets. Five evaluation indicators are statistically analyzed to prove the feasibility and effectiveness of the proposed algorithm. Abstract : An edge thinning algorithm is proposed based on the newly defined single‐pixel connectiong patterns to obtain singel‐pixel wide and contineous edge.